Comparison of 2% chlorhexidine and 5.25% sodium hypochlorite irrigating solutions on postoperative pain: A randomized clinical trial - Bashetty Kusum; Hegde Jayshree (Wolters Kluwer Medknow Publications, 2010)
Aim: To compare the levels of postoperative pain after cleaning and shaping of root canals using two different root canal irrigants for debridement. Materials and Methods: Forty patients with irreversible pulpitis, pulp necrosis and non-vital teeth exhibiting acute apical periodontitis requiring root canal treatment were included. At random, canals were cleaned and shaped with the following protocols. 2% chlorhexidine solution in group I and 5.25% sodium hypochlorite solution in group II were used as an irrigants. Access cavities were closed with a sterile cotton pellet and cavit. The patients recorded degree of pain at various time intervals after cleaning and shaping on a visual analogue scale for 1 week. Results: The mean pain score for group I was between 0.65 and 3.35 and for group II was between 0.95 and 4.50. There was significant difference in the pain level between the two groups only at 6 th hour postoperatively (P<0.05) and the pain was more in sodium hypochlorite group. Conclusions: More pain was present in teeth irrigated using 5.25% sodium hypochlorite when compared to that in teeth irrigated using 2% chlorhexidine solution. Significant difference in pain level was present only at 6th hour postoperatively, and at all other periods (24 th hour, 4 th and 7 th days) there was no significant difference in pain level between the two groups.